Multi-Criteria Spatial Analysis and Accessibility Assessment for Optimizing Public Electric Vehicle Charging Station (EVCS) Locations in Bandung City - An An Anisarida; Syapril Janizar (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: The transition toward low-carbon transportation and the growing commitment to achieving Net Zero Emissions (NZE) have increased the importance of electric vehicle adoption in Indonesia. In Bandung City, however, the spatial distribution of Public Electric Vehicle Charging Stations (EVCS) remains concentrated in central urban areas, creating disparities in service coverage across different districts. Objective: This study aims to identify priority areas for EVCS development in Bandung City by integrating spatial and multi-criteria analyses. Methods: A quantitative GIS-based approach was employed by combining spatial distribution analysis, buffer analysis (3 km and 5 km), accessibility assessment, service gap analysis, and the Analytical Hierarchy Process (AHP). AHP weights were obtained from pairwise comparisons by eight experts from PLN, the Bandung City Transportation Agency, urban planning practitioners, and academics, aggregated using the geometric mean. Results: The findings reveal that EVCS facilities are concentrated in the city center, with 32 of 64 units (50.00%) located in central districts and 11 units (17.19%) along the Soekarno-Hatta corridor. AHP weighting produced population density 0.40, accessibility 0.30, distance from existing EVCS 0.20, and proximity to activity centers 0.10, with a Consistency Ratio of 0.08. Weighted overlay yielded the highest suitability scores for Gedebage (4.72) and Cibiru (4.58), followed by Rancasari (4.41), Arcamanik (4.27), and Cinambo (4.15). Conclusion: The GIS-AHP framework translates spatial inequity into a ranked development priority list, giving PLN, local government, and infrastructure investors an evidence-based instrument for allocating charging capacity equitably and for embedding service-equity criteria into sustainable transportation and energy transition policy.